An Analytical Approach for Decision-Making - Sakshi Aggarwal; Shrddha Sagar (JOIV : International Journal on Informatics Visualization, 2018)
In this complex world, coping with daily problems is quite tedious. The more advancement in technology means more difficulties in decision-making process. Hence some analytical tools are needed to deal with improvement in decisions being made. A classic AHP model enables us to make efficient decision by reducing the complex issues. It takes multiple parameters into consideration. One of the area where decision-making is quite a tough job is Politics. Selection of the electoral party in any elections, be it Lok Sabha elections or Rajya Sabha elections, has been a matter of discussion for the voters as well as the media. The decisions are reflected when uncertainties are added in the opinions of the domain experts due to multiple parameters.Â  In this paper we have proposed a model for rectifying the uncertainties using multi criteria decision analysis and analytic hierarchy process (AHP).